ASSESSMENT OF FAECAL SLUDGE HYGIENE BASED ON HM CONCENTRATIONS AND HELMINTH INFECTION LEVELS: INFLUENCE OF ONSITE CONTAINMENT PIT TECHNOLOGIES AND USER CATEGORIES IN DAR ES SALAAM (The Journal of Building and Land Development, 2024)
This study investigated HM and microbial contamination in faecal sludge collected from various onsite sanitation systems, including pit latrines, septic tanks, and cesspits, across different user categories (commercial, industrial, institutional, and domestic) in Dar es Salaam city, Tanzania. The research hypothesized that the type of pit technology and user category would significantly impact HM concentrations in the sludge. Samples were analyzed for HM contents in both total solids and filtrate using standardized examination methods. Results indicated that HM concentrations in the faecal sludge ranged from 0.04 to 40.99mg/kg in total solids, while filtrate concentrations ranged from below detection limits (0.001 mg/L) to 0.430 mg/L. Zn consistently showed the highest concentrations across all categories. Contrary to expectations, statistical analysis revealed no significant differences in HM levels based on pit type or user category (P â‰¥ 0.05). While the HM concentrations were within USEPA regulatory limits for land application. They however, exceeded levels typically excreted by humans, indicating potential contamination within the onsite systems calling for upstream control of contamination. Additionally, the presence of helminth eggs, particularly Ascaris lumbricoides and hookworms, exceeded WHO and Tanzanian safety standards for agricultural reuse, underscoring the need for proper treatment before faecal sludge application to mitigate health risks.Â Keywords: Hygiene value; Pit technology types; Pit user type; Resource recovery